Lower Prevalence of Osteoporosis in Patients with COPD Taking Anti-Inflammatory Compounds for the Treatment of Diabetes: Results from COSYCONET - Kahnert K; Jörres RA; Lucke T; Trudzinski FC; Mertsch P; Bickert C; Ficker JH; Behr J; Bals R; Watz H; Welte T; Vogelmeier CF; et al. (International Journal of COPD, 2021)
Kathrin Kahnert,1 Rudolf A Jörres,2 Tanja Lucke,2 Franziska C Trudzinski,3 Pontus Mertsch,1 Christiane Bickert,1 Joachim H Ficker,4 Jürgen Behr,1 Robert Bals,5 Henrik Watz,6 Tobias Welte,7 Claus F Vogelmeier,8 Peter Alter8 On behalf of COSYCONET Study Group1Department of Medicine V, University Hospital, LMU Munich, Comprehensive Pneumology Center Munich (CPC-M), Member of the German Center for Lung Research (DZL), Munich, Germany; 2Institute and Outpatient Clinic for Occupational, Social and Environmental Medicine, University Hospital, LMU Munich, Comprehensive Pneumology Center Munich (CPC-M), Member of the German Center for Lung Research (DZL), Munich, Germany; 3Department of Pneumology and Critical Care Medicine, Thoraxklinik, University of Heidelberg, Translational Lung Research Center Heidelberg (TLRC-H), Member of the German Center for Lung Research (DZL), Heidelberg, Germany; 4Department of Respiratory Medicine, Nürnberg General Hospital, Paracelsus Medical University, Nürnberg, Germany; 5Department of Internal Medicine V - Pulmonology, Allergology, Intensive Care Medicine, Saarland University Hospital, Homburg, Germany; 6Pulmonary Research Institute at LungenClinic Grosshansdorf, Airway Research Center North (ARCN), Member of the German Center for Lung Research (DZL), Grosshansdorf, Germany; 7Clinic for Pneumology, Hannover Medical School, Member of the German Center for Lung Research (DZL), Hannover, Germany; 8Department of Medicine, Pulmonary and Critical Care Medicine, University of Marburg (UMR), Germany, Member of the German Center for Lung Research (DZL), Marburg, GermanyCorrespondence: Kathrin KahnertDepartment of Medicine V, University Hospital, LMU Munich, Comprehensive Pneumology Center Munich (CPC-M), Member of the German Center for Lung Research (DZL), Munich, GermanyTel +49 89 4400 52590Fax +49 89 4400 54905Email kathrin.kahnert@med.uni-muenchen.deBackground: Patients with chronic obstructive pulmonary disease (COPD) often have osteoporosis and diabetes as comorbid conditions. Anti-diabetic medication, including metformin, has protective effects on osteoporosis in experimental studies. We therefore studied whether patients with COPD receiving anti-diabetic medication had a lower osteoporosis prevalence in a large COPD cohort, COSYCONET.Methods: Assessment of osteoporosis was based on patients’ reports of physician-based diagnoses and the presence of disease-specific medication. The predictive value of physical characteristics, lung function, comorbidities, cardiovascular medication, and the use of anti-inflammatory diabetes medication, including metformin, sulfonylureas, glinides or DPP4I, was evaluated using logistic regression analysis. ClinicalTrials.gov: NCT01245933.Results: In total, 2222 patients were eligible for analysis (863 [39%] female, mean age 65 y), 515 of whom had higher symptoms and exacerbations (Global Initiative for Chronic Obstructive Lung Disease group D). Osteoporosis was present in 15.8% of the overall cohort, and in 24.1% of GOLD D patients. Regression analyses identified the following as associated with osteoporosis (p < 0.05): female sex, higher age, lower body-mass index, asthma, higher air trapping, oral steroids, and cardiovascular medication. Although oral anti-diabetic medication was overall not associated with a lower prevalence of osteoporosis (p = 0.131), anti-inflammatory anti-diabetic medication (p = 0.009) and metformin-containing therapy (p = 0.039) were. This was driven by GOLD D patients.Conclusion: In a large COPD cohort, anti-inflammatory diabetes therapy, including metformin, was associated with a lower prevalence of osteoporosis, especially in patients with higher symptoms and exacerbations. These findings suggest a protective effect of common anti-diabetic medication on osteoporosis, possibly as a result of attenuated systemic inflammation.Keywords: chronic obstructive pulmonary disease, oral corticosteroids, inhaled corticosteroids, anti-inflammatory, metformin, diabetes